Efficacy of Flaxseed and Fish Oils on Adults with Rheumatoid Arthritis - Safeena Amjad; Nighat Ahmad; Asma Afreen; Shazia Ashraf; Zaheer Ahmad (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the relative efficacy of flaxseed and fish oils in the management of rheumatoid arthritis. Methods: The comparative study was conducted in the outpatient department of Rheumatology at Fatima Memorial Hospital, Shadman, Lahore, Pakistan, from July to December 2017, and comprised rheumatoid arthritis patients who were divided into group A receiving 3g/day of flaxseed oil and group B receiving 3g/day of fish oil for 90 days. Blood samples were taken at baseline and post-intervention to note the difference on biochemical parameters. Data was analysed using SPSS 21. Results: Of the 60 patients, there were 30(50%) in each of the two groups. Overall, there were 8(13.3%) males and 52(86.7%) females. Both groups showed significant change in all biochemical parameters compared to baseline values (p<0.05). Intergroup comparison showed that flaxseed oil treatment was significantly more effective than fish oil treatment (p<0.05). Conclusion: While both forms of intervention were found to be effective, flaxseed oil was significantly more effective than fish oil in reducing the inflammation of joints in rheumatoid arthritis patients. Keywords: Rheumatoid arthritis, Synovial joints, Flax, Fish oil, Omega 3 fatty acids.